Age and Growth of European Sardine (Sardina pilchardus) in the Central Mediterranean Sea: Implication for Stock Assessment - Basilone, Gualtiero; Ferreri, Rosalia; Bonanno, Angelo; Genovese, Simona; Barra, Marco; Aronica, Salvatore (Fishes, 2023)
Understanding the drivers of fish growth is essential for predicting productivity, stability, and resilience of exploited populations. For the European sardine (Sardina pilchardus) in the Strait of Sicily (Central Mediterranean Sea, GSA16), growth parameters or length at age estimates have never been published before. To fill this data gap, the length and age as well as the von Bertalanffy parameters (the most widely used growth model) were estimated. Data from landing samples during the period 2009–2019 were collected by two methods (purse seine and mid-water pelagic trawl). Temporal trends in average length at age, as well as an overall age-length key were obtained and compared with other areas across the geographical distribution range of sardine in the Mediterranean Sea. The observed age range was 0–3 years with most of the individuals belonging to Age 1 (52%) and Age 2 (43%). The mean length at age, for the entire study period, was 11.7 (±0.08) cm for Age 0; 13.4 (±0.09) cm for Age 1; 15 (±0.1) cm for Age 2; and 16.6 (±0.11) cm for Age 3. Furthermore, during the considered period, a reduction in the length at age was observed in the older classes (Age 2 and Age 3). The estimated parameters of the von Bertalanffy growth model were Linf = 18 (±1.15) cm, K= 0.459 (±0.018), and t0 = −1.99 (±0.008) and, accordingly, the mortality vector was obtained according to Gislason’s model, for each age class, these values were 0.99 (0.98–1.02) C at Age 0; 0.71 (0.7–0.73) y−1 at Age 1; 0.6 (0.59–0.62) y−1 at Age 2; 0.54 (0.53–0.56) y−1 at Age 3; and 0.51 (0.49–0.53) y−1 at Age 4. Results appeared in agreement with literature from other areas of the Mediterranean Sea and suggested a poor condition status of the sardine stock in the GSA16.